2021
DOI: 10.1007/s11482-021-09985-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Positive Parenting Styles on Self-Regulated Learning in Chinese Adolescents Testing the Mediating Effects of Self-Esteem

Abstract: The positive parenting styles and the self-esteem of the parents are two factors that affect Self-regulated learning (SRL). Moreover, the variable of self-esteem is influenced by the positive parenting styles. However, previous studies have investigated only the cross-sectional relationship between positive parenting styles and SRL and that between positive parenting styles and self-esteem. This study explored the relationship between positive parenting styles and self-regulated learning in Chinese adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The findings of the study showed that parental bonding predicts self-regulation, proactive attitude, and academic performance in students. These findings are in line with the previous literature suggesting that strong parental bonding has been proved to enhance teenage self-esteem and significantly influence their self-regulation abilities (Du, Jian, Hua, & Qi, 2021). Moilanen, Padilla-Walker, and Blaacker (2018) studied different dimensions of self-regulation, both long term and short term among the adolescent population.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the study showed that parental bonding predicts self-regulation, proactive attitude, and academic performance in students. These findings are in line with the previous literature suggesting that strong parental bonding has been proved to enhance teenage self-esteem and significantly influence their self-regulation abilities (Du, Jian, Hua, & Qi, 2021). Moilanen, Padilla-Walker, and Blaacker (2018) studied different dimensions of self-regulation, both long term and short term among the adolescent population.…”
Section: Discussionsupporting
confidence: 91%
“…The relation between self-esteem and metacognitive engagement has also been verified, as shown in a study by Du and colleagues [ 46 ], who analyzed how students used self-regulated learning (considered a metacognitive strategy) to solve a specific task. Their results confirmed that self-esteem was a factor influencing students’ ability to self-regulate learning.…”
Section: Theoretical Backgroundmentioning
confidence: 74%
“…Moreover, adolescents' smartphone addiction can threaten psychological well-being, aggravate depression, promote low self-esteem and fear of rejection, and impede interpersonal relationship formation and development [13]. Adolescents who are highly dependent on smartphones and active in the cyberspace for a signi cant amount of time tend to witness or experience victimization by cyberbullying; exposure to such cyber environments enables adolescents to encounter threats such as perpetrators [2].…”
mentioning
confidence: 99%
“…Adolescents who are highly dependent on smartphones and active in the cyberspace for a signi cant amount of time tend to witness or experience victimization by cyberbullying; exposure to such cyber environments enables adolescents to encounter threats such as perpetrators [2]. Positive parenting is an important factor that can change adolescents' psychological and behavioral characteristics [13], is closely related to adolescents' smartphone addiction, and can be an important variable to mediate the risk of becoming a perpetrator of cyberbullying [4,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation